Emotion, Science and Rationality: The Case of the Brent Spar. (1st August 1999) - Huxham, M.; Sumner, D.
Abstract : In June 1995, a campaign by Greenpeace forced the multinational oil company Shell to cancel its planned disposal of a redundant oil installation in the Atlantic. The Brent Spar incident attracted massive publicity and was influential in changing government policy on marine disposal of waste. During and following their campaign, Greenpeace were criticised as emotive and irrational by Shell and academic scientists. This paper looks at the arguments used during the debate, using literature, interviews and questionnaires. We investigate the use of key environmental words and phrases and ask what is meant by rationality in this context. We discuss some of the lessons that should be learnt from the incident by policy makers and scientists.